Dialectics of Jurisprudence, Science, and Tradition Analysis of the Accuracy of the Qibla Direction of Sentot Ali Basya Cemetery - Badrut Taman; Doki Hermansyah; Harahap, Rindom; Agutini; Japarudin; Imam Mahdi (Islamic Research Publiser, 2023)
This research examines the direction of the old grave of Sentot Ali Basya, which tends to accurately align with the qibla compared to the new cemetery in the city of Bengkulu. The ironic condition where the qibla direction in the new cemetery cannot be as accurate as the old cemetery becomes the uniqueness of this study. Data on the accuracy of the qibla direction in the cemetery were obtained through field observations, while social-religious data related to the development of fiqh schools, the level of knowledge, and Islamic traditions in the community of Bengkulu were explored through historical literature on Islam in Bengkulu. This research found that the people of Bengkulu in 1885, the year of Sentot Ali Basya's death, already had a high civilization in the fields of fiqh, science, and tradition. The people of Bengkulu in the 19th century adhered to the Shafi'i fiqh school. This school entered Bengkulu through preachers, including Sentot Ali Basya. In this school, rules regarding the qibla direction of the deceased were highly regarded, to the extent that a corpse not facing the qibla had to be reoriented towards the qibla, even if it required exhuming the grave. In terms of science, knowledge of navigation was still prevalent among the people of Bengkulu, partly because many residents worked as fishermen and also due to the indirect contribution of navigation methods, including the qibla direction, brought by traders sailing to Bengkulu.